2019
DOI: 10.5897/jat2019.0349
|View full text |Cite
|
Sign up to set email alerts
|

The influence of tax amnesty programme on tax compliance in Nigeria: The moderating role of political trust

Abstract: The paper examined the influence of tax amnesty programme on tax compliance in Nigeria moderating the effect of political trust. The survey research design was employed to understand the taxpayer's perception of the Voluntary Assets and Income Declaration Scheme (VAIDS). We collected the data through the administration of questionnaires to taxpayers across the most commercial states in Nigeria. The data obtained were analysed using the frequency table, the Cronbach alpha test, and the binary logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…Wartick, M. and Mark (1992) study on detection probability and tax compliance found tax attitude and perception to greatly influence taxpayer compliance behaviour. The tax attitudinal and perception factors include fairness and equity in the distribution of tax proceeds, trustworthiness and accountability for taxes collected by the government, the peer influence of other taxpayers and the moral obligation of the taxpayer to render complete tax returns (Okoye, 2019;Sapiei et al, 2014;Wartick, M. & Mark, 1992). Torgler (2012) established an association between trust and tax compliance morale.…”
Section: H 3 : Increase In Tax Compliance Costs Increases the Likelihood Of Tax Non-compliance Behaviour Of Smesmentioning
confidence: 99%
“…Wartick, M. and Mark (1992) study on detection probability and tax compliance found tax attitude and perception to greatly influence taxpayer compliance behaviour. The tax attitudinal and perception factors include fairness and equity in the distribution of tax proceeds, trustworthiness and accountability for taxes collected by the government, the peer influence of other taxpayers and the moral obligation of the taxpayer to render complete tax returns (Okoye, 2019;Sapiei et al, 2014;Wartick, M. & Mark, 1992). Torgler (2012) established an association between trust and tax compliance morale.…”
Section: H 3 : Increase In Tax Compliance Costs Increases the Likelihood Of Tax Non-compliance Behaviour Of Smesmentioning
confidence: 99%
“…According to Hite and Roberts (1992) and Vincent (2021), the perception of fairness has a strong correlation with the perception of an improved tax system and dissuades taxpayers from deciding on non-compliance. Determinants of tax attitudes and perceptions are fairness and equity in fiscal revenue distribution, trustworthiness and accountability for taxes collected by the government, the peer influence of other taxpayers, and the taxpayer’s moral obligation to file complete tax returns (Francis, 2019; Sapiei et al, 2014; Vincent, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As shown by previous research (Ad Qisthon, 2021).MSME taxpayer compliance is influenced by tax knowledge and accounting mentality. The accounting mentality, trust and power of revenue authorities have been proven to have an impact on MSME taxpayer compliance (Mutanga Marcus, 2021).According to research (Hikmah, 2021),accounting mentality has no effect on taxpayer compliance. (Deo, Pamujiku Putra;Pakpahan, Yunus;Tampubolon, 2022) shows that MSME taxpayer compliance is influenced by tax knowledge and the level of taxpayer trust.…”
Section: Introductionmentioning
confidence: 99%